2010
DOI: 10.3390/s101109808
|View full text |Cite
|
Sign up to set email alerts
|

Optical Sensing with Simultaneous Electrochemical Control in Metal Nanowire Arrays

Abstract: This work explores the alternative use of noble metal nanowire systems in large-scale array configurations to exploit both the nanowires’ conductive nature and localized surface plasmon resonance (LSPR). The first known nanowire-based system has been constructed, with which optical signals are influenced by the simultaneous application of electrochemical potentials. Optical characterization of nanowire arrays was performed by measuring the bulk refractive index sensitivity and the limit of detection. The forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…[40][41][42][43] We have recently worked on implementing electrochemistry with various plasmonic nanostructures such as gold colloids 39 and gold nanowire arrays. 44 In this study, we perform high resolution spectroscopy 12,14 synchronized with CV scans using two other types of plasmonic nanostructures as working electrodes, namely gold nanodisks 13,14 fabricated on ITO 40 (supporting nanoparticle plasmons) and short-range ordered nanoholes in a thin gold film 12,22,40,45 (supporting surface plasmons). These structures are known in the plasmonics research field, but have not previously been combined with electrochemistry except in one recent study where we demonstrated electrochemical recrystallization.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42][43] We have recently worked on implementing electrochemistry with various plasmonic nanostructures such as gold colloids 39 and gold nanowire arrays. 44 In this study, we perform high resolution spectroscopy 12,14 synchronized with CV scans using two other types of plasmonic nanostructures as working electrodes, namely gold nanodisks 13,14 fabricated on ITO 40 (supporting nanoparticle plasmons) and short-range ordered nanoholes in a thin gold film 12,22,40,45 (supporting surface plasmons). These structures are known in the plasmonics research field, but have not previously been combined with electrochemistry except in one recent study where we demonstrated electrochemical recrystallization.…”
Section: Introductionmentioning
confidence: 99%
“…The raw optical response data were normalized with the reference light. All scattering spectra were obtained at a specific potential value of 0.5 V (vs. Ag/AgCl) during the cathodic process (1.0 V → −0.2 V, vs. Ag/AgCl) in order to exclude the effects of applied potential and the direction of sweep on the scattering characteristics (Figure S3 in the Supplementary materials)24.…”
Section: Methodsmentioning
confidence: 99%
“…A positively charged polyethyleneimine (PEI) was then used to adhere the negatively charged DNA-coated gold particles to the substrate [22,23]. The final lift-off in acetone and water resulted in clearly defined particle lines that were not dense enough for electrical conduction [12,14]. The width of the lines is determined by lithography, but the height of the nanowire depends mainly on the size of the nanoparticles and the duration of subsequent gold enhancement.…”
Section: Methodsmentioning
confidence: 99%